1986
DOI: 10.1007/bf00251057
|View full text |Cite
|
Sign up to set email alerts
|

Acute response of testicular interstitial tissue in rats to the cytotoxic drug ethane dimethanesulphonate

Abstract: The cytotoxic effects of ethane dimethanesulphonate upon rat Leydig cells were examined ultrastructurally up to 3 days after treatment and related to changes in serum levels of gonadotrophins and testosterone. Six hours after administration of ethane dimethanesulphonate the usual tubulo-vesicular morphology of Leydig-cell smooth endoplasmic reticulum was converted to small vesicles and the Golgi apparatus showed focal hypertrophy into anastomosing tubules. These changes became more marked by 12 h with many Ley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Therefore, this process clearly was not affected by the thyroid status of the rat. Similar to previously published reports [17,18,[23][24][25][26][27][28][29][30][31], no Leydig cells were detected in the present study during the first 2 wk following EDS administration, but Leydig cells were seen at Day 21. Evidence has also been presented previously [24,27] for a mesenchymal origin for the newly formed Leydig cells in the EDS-treated rat testis, and their site of differentiation has been described as peritubular and perivascular.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, this process clearly was not affected by the thyroid status of the rat. Similar to previously published reports [17,18,[23][24][25][26][27][28][29][30][31], no Leydig cells were detected in the present study during the first 2 wk following EDS administration, but Leydig cells were seen at Day 21. Evidence has also been presented previously [24,27] for a mesenchymal origin for the newly formed Leydig cells in the EDS-treated rat testis, and their site of differentiation has been described as peritubular and perivascular.…”
Section: Discussionsupporting
confidence: 89%
“…Based on these findings, we suggest that the peritubular mesenchymal cells are the principal, if not the only, precursor cells for the new generation of Leydig cells in the EDS-treated adult rats. Similarly, peritubular mesenchymal cells have been observed as the precursor cells for the adult Leydig cells in prepubertal rat testis [2,19,23,32], except for one report that suggests the mesenchymal cells in the central interstitium as the Leydig cell precursors [33]. It is difficult for us to accept this suggestion, however, which is contradictory to the findings of many others in the field, especially because this statement has not been justified in the said study [33] or in a followup study using appropriate markers to identify these precursor cells [34].…”
Section: Discussionmentioning
confidence: 97%
“…Taken together, these data with the rabbit are consistent with the effects seen in the rat [7,25], in that T production was impaired after LH binding and before cholesterol side-chain cleavage. Finally, there is considerable research in the rat to indicate that EDS acts directly on the Leydig cell to reduce its capacity to produce T, cause ultrastructural damage, and eventually kill the cell [2,3].…”
Section: Fig 3 A) Electron Micrograph Of Adult Rabbit Leydig Cells mentioning
confidence: 98%
“…In vivo exposure to 75-100 mg/kg ethane-dimethanesulfonate (EDS) selectively kills Leydig cells in adult rat testes [1][2][3][4][5][6]. Degenerative changes are seen histologically within 6 h after dosing.…”
Section: Introductionmentioning
confidence: 98%
“…Although EDS destroys the Leydig cells in the testis of the adult Bartlett & Donachie, 1986;Morris et al 1986) and neonatal rat (Kerr, Risbridger & Knell, 1988;Zaidi, Lendon, Dixon & Morris, 1988), it has been reported that in the adult rat a further chal¬ lenge with EDS is not cytotoxic to the regenerating population of immature Leydig cells (Morris, 1985;Kerr & Knell, 1987). Since Leydig cells of immature rat testes are also reported to be resistant to the cytocidal effect of EDS (Molenaar, de Rooij, Rommerts et al 1985;Morris, 1985;Rommerts, Grootenhuis, Hoogerbrugge & van der Molen, 1985) maturational changes might be involved in the development of sus¬ ceptibility to EDS toxicity.…”
Section: Introductionmentioning
confidence: 95%